Effects of remifentanil on esophageal and esophagogastric junction (EGJ) bolus transit in healthy volunteers using novel pressure‐flow analysis. Issue 2 (18th August 2017) - Cock, C.; Doeltgen, S. H.; Omari, T.; Savilampi, J.
Abstract: Background: Remifentanil is associated with subjective dysphagia and an objective increase in aspiration risk. Studies of opioid effects have shown decreased lower esophageal sphincter relaxation. We assessed bolus transit through the esophagus and esophagogastric junction (EGJ) during remifentanil administration using objective pressure‐flow analysis. Methods: Data from 11 healthy young participants (23±3 years, 7 M) were assessed for bolus flow through the esophagus and EGJ using high‐resolution impedance manometry (Manoscan™, Sierra Scientific Instruments, Inc., LES Angeles, CA, USA) with 36 pressure and 18 impedance segments. Data were analyzed for esophageal pressure topography and pressure‐flow analysis using custom Matlab analyses (Mathworks, Natick, USA). Paired t tests were performed with a P ‐value of < .05 regarded as significant. Key Results: Duration of bolus flow through (remifentanil/R 3.0±0.3 vs baseline/B 5.0 ± 0.4 seconds; P  < .001) and presence at the EGJ (R 5.1 ± 0.5 vs B 7.1 ± 0.5 seconds; P  = .001) both decreased during remifentanil administration. Distal latency (R 5.2 ± 0.4 vs B 7.5 ± 0.2 seconds; P  < .001) and distal esophageal distension‐contraction latency (R 3.5 ± 0.1 vs B 4.7 ± 0.2 seconds; P  < .001) were both reduced. Intrabolus pressures were increased in both the proximal (R 5.3 ± 0.9 vs B 2.6 ± 1.3 mm Hg; P  = .01) and distal esophagus (R 8.6 ± 1.7 vs B 3.1 ± 0.8 mm Hg; P  = .001). There was no evidence of increased esophageal bolus residue. Conclusions and Inferences: Remifentanil‐induced effects were different for proximal and distal esophagus, with a reduced time for trans‐sphincteric bolus flow at the EGJ, suggestive of central and peripheral μ‐opioid agonism. There were no functional consequences in healthy subjects. Abstract : The mu‐opioid receptor agonist remifentanil produced different physiological effects in the proximal and distal esophagus. Contractile vigor was reduced in the proximal and distal latency was reduced in the distal esophagus with unchanged contractility. Bolus transit remained intact resulting in increased intrabolus pressure due to shorted available time for transit.